2017
DOI: 10.1108/ccsm-11-2015-0159
|View full text |Cite
|
Sign up to set email alerts
|

Family and state ownership, internationalization and corporate board-gender diversity

Abstract: Purpose In times of vivid debates on the inclusion of women on boards, the purpose of this paper is to shed a new light on the composition of boardrooms in emerging market firms by investigating how family and state ownership affect board-gender diversity in the emerging economies. Design/methodology/approach This study uses Tobit regression to examine the effect of firm ownership on board-gender diversity. A panel data set of Chinese and Indian firms for the period 2004-2013 is used to conduct this study. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 47 publications
0
29
0
1
Order By: Relevance
“…Given the specific distribution of our dependent variable, we applied the left and right-censored Tobit regression model. Tobit models are commonly used to study censored data and are more powerful than many other regression models in these cases (Saeed et al, 2017;Zhou, 2019).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the specific distribution of our dependent variable, we applied the left and right-censored Tobit regression model. Tobit models are commonly used to study censored data and are more powerful than many other regression models in these cases (Saeed et al, 2017;Zhou, 2019).…”
Section: Methodsmentioning
confidence: 99%
“…In order to have a deeper understanding of the relationship between implicit need for achievement, risk perception, and internationalization, we included several control variables suggested by prior studies. We included gender (0 = Male, 1 = Female) because Saeed, Yousaf, and Alharbi (2017) argued that female directors have a positive impact on the internationalization of the firm and Falkner and Hiebl (2015) found that male entrepreneurs show a greater interest toward risks. Age of participants, age of firms, size of firms, educational level and sector of industry (Acedo & Florin, 2006;Cavusgil & Naor, 1987;Coviello & Jones, 2004;Hsu et al, 2013;Wiklund & Shepherd, 2003) were included because these variables represent the experience of participants in taking up challenging business decision.…”
Section: Control Variablesmentioning
confidence: 99%
“…On the one hand, some scholars find a positive relationship on firms from Anglo‐Saxon countries (Saeed et al, 2016), Europe (Bianco, Ciavarella, & Signoretti, 2015), and Malaysia (Abdullah, 2014), which is likely to be motivated by a more inclusive environment characterizing family firms (e.g., Ruigrok, Peck, & Tacheva, 2007; Sheridan & Milgate, 2005). On the other hand, others show a negative relationship (Saeed et al, 2017), indicating that family culture and traditions, primogeniture succession, and the secondary role of females in the family may prevent female owners from gaining leadership positions and exercise influence on the board (Abdullah et al, 2016). This can perhaps explain why having female chairs in family firms is associated with lower financial performance (Nekhili, Chakroun, & Chtioui, 2018).…”
Section: Current State Of the Fieldmentioning
confidence: 99%
“…Our review shows that different types of owners have different preferences toward gender diversity on the board. Regardless of the institutional context, state‐owned firms are associated with fewer female directors on boards (Farag & Mallin, 2016; Saeed, Belghitar, & Yousaf, 2016; Saeed, Yousaf, & Alharbi, 2017). In addition, previous studies suggest that state ownership intensifies the positive effect of board gender diversity on post‐IPO returns (McGuinness, 2018) and dividend payout (Saeed & Sameer, 2017).…”
Section: Current State Of the Fieldmentioning
confidence: 99%
“…This typology has yet to be examined with larger, cross-cultural samples, but may offer a useful model for subsequent research (Panjalingan, 2012) [83]. Saeed, Yousaf & Alharbi (2017) [84] offer useful findings on women managers in family-led firms: when such firms expand internationally or are awarded state contracts (in India and China), women managers and male directors both gain status and power. In Pakistan too, despite ideals concerning the inclusive ethics of a Muslim economic enterprise which gives equal participation to women (Ahmad, 2004) [64], in practice the education of women (and their high rates of illiteracy) compares unfavourably with that of men, and very few Pakistani women achieve professional or managerial status.…”
Section: Women's Role In Traditional Islamic Muslim-majority Culturesmentioning
confidence: 99%